Social media use improves executive functions in middle-aged and older adults: A structural equation modeling analysis - KHOO, Shi Ann Shuna (Institutional Knowledge at Singapore Management University, 2020)
Given the paucity of research on the cognitive implications of social media use in middle and late adulthood, we sought to understand the relations between middle-aged and older adults' social media use and their executive functions (EF)—a set of domain-general cognitive control processes—and the underlying mechanism. By analyzing a nationally representative cohort ranging from ages 40s–70s from the MIDUS Refresher Survey and Cognitive Project, we tested a serial mediation model with perception of social support and sense of control (i.e., personal mastery and perceived constraints) as sequential mediators in a structural equation modeling analysis. We found that perceived social support and constraints fully and serially mediated the relation of middle-aged and older adults' social media use for interpersonal interactions with EF. Our study demonstrates that middle-aged and older adults’ social media use for social connection can be a useful medium that protects against age-related cognitive decline in EF.